Frankissstein : a love story - Winterson, Jeanette, 1959- (Grove Press, 2019)
"Lake Geneva, 1816. Nineteen-year-old Mary Shelley is inspired to write a story about a scientist who creates a new life-form. In Brexit Britain, a young transgender doctor called Ry is falling in love with Victor Stein, a celebrated professor leading the public debate around AI and carrying out some experiments of his own in a vast underground network of tunnels. Meanwhile, Ron Lord, just divorced and living with his mom again, is set to make his fortune launching a new generation of sex dolls for lonely men everywhere. Across the Atlantic, in Phoenix, Arizona, a cryogenics facility houses dozens of bodies of men and women who are medically and legally dead... but waiting to return to life. What will happen when homo sapiens is no longer the smartest being on the planet? In fiercely intelligent prose, Jeanette Winterson shows us how much closer we are to that future than we realize. Funny and furious, bold and clear-sighted, Frankissstein is a love story about life itself"--